USABILITY OF IRON (II)-HYDROGEN PEROXIDE IN THE COD REDUCTION OF A STRONG WASTEWATER - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 1993)
The hydrogen peroxide-iron(II) system was used to hydroxylate and to oxidize the refractory organic materials in a strong wastewater with mean COD of 14000. The relations between the COD of water and the reagents were established to get higher COD removal yields.
Keywords: Pharmaceutical wastewater; hydrogen peroxide; oxydation; COD removal; iron(II)